Recaídas en Hanseniasis: experiencia personal - Aguas, José Terencio de Las (1999)
Thirty-one relapses were observed among 451 patients treated with sulphones and 15 of them were of the dimorphous form. The time elapsed between regression of lesions and the relapses range from 6 to 39 years. Only one relapsed case was observed among the patients traced with MDT/WHO regimens.